(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
In this article I extract from the work of Stefano Rodotà what may be described as his philosophy of law and of technology. I will be analysing his writings from the last couple of decades, when the national and international debate on bioethics and biolaw was especially vibrant. In these writings Rodotà takes on the question of the challenges that established and settled law has been confronting in the face of technological innovation, while outlining a policy framework for the new rights that were emerging in the process. In carrying out this analysis I highlight the way the developing technology has been changing our personal lives and models of social organization, while also addressing the institutional response to these changes.